Isotopic niche partitioning between two small cetacean species - Durante, Cristian Alberto; Crespo, Enrique Alberto; Loizaga de Castro, Rocio (Marine Ecology Progress Series)
Commerson’s dolphin Cephalorhynchus commersonii and Peale’s dolphin Lageno - rhynchus australis live in sympatry along the southwestern South Atlantic Ocean, suggesting the existence of some degree of habitat partitioning to reduce their competition for resources. Both species are usually associated with coastal environments, but information on their trophic ecology is scarce. Here we explored the existence of trophic resource partitioning between these 2 sympatric species using δ13C and δ15N. From 2007 to 2013, we analyzed a total of 14 Commerson’s dolphin and 34 Peale’s dolphin skin samples from a marine protected area in Argentina. Significant differences in δ13C values indicated intra- and interspecific spatial partitioning. Three different Peale’s dolphin feeding groups (FGs) were identified: FG1 exclusively exploited the pelagic habitat, FG2 occupied more pelagic/inshore habitats (similar to Commerson’s dolphins), and FG3 occupied more benthic/inshore habitats. Isotopic niche breadth varied between species and feeding groups, exhibiting less variation in prey selection among Commerson’s dolphins. According to Bayesian standard ellipse area analysis, isotopic niche overlap was found between FG2 and FG3 from 2007 to 2012, and between FG2 and Commerson’s dolphins. Mixing models suggest that FG3 has a diet mainly based in benthic fish, while FG2 and Commerson’s dolphins feed predominantly on pelagic fish. Overall, this study indicates segregation in the use of trophic resources between 2 sympatric dolphin species, showing different foraging strategies that promote coexistence and reduce intra- and interspecific competition. Furthermore, the presence of 3 Peale’s dolphin feeding groups segregated at a small geographic scale suggests a previously unknown ecological complexity. Fil: Durante, Cristian Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Crespo, Enrique ...